Peningkatan Ekspektasi Positif Masyarakat terhadap Pendidikan di Mts Al-Khairiyah Batu Gajah - Susanti,, Susanti,; Kusen, Kusen; Rini, Rini (JOEAI (Journal of Education and Instruction), 2021)
This study aims to see how to increase the positive expectations of the community towards education at MTs Al-Khairiyah Batu Gajah. The research is descriptive using qualitative methods. The technique used in this research is observation, interview, and documentation. This study uses an inductive method to test the confidence of the data using triangulation of sources, methods and time. The results of the study, obtained the following information; 1) The school's efforts to increase community expectations are to improve the quality of learning through structured learning activities consisting of planning, implementation, and evaluation; 2) People's expectations of education at MTs Al-Khairiyah Batu Gajah are very enthusiastic, people hope that their children who have been entrusted to MTs Al-Khairiyah can produce the expected results in accordance with the goals and have good character; 3) Factors that influence people's expectations of education at MTs Al-Khairiyah, are the existence of Student Da'wah Institutions (LDK), and drum band extracurricular factors, because these factors are often held in public activities in the community both in schools, villages and in the community. outside the village. This factor is the most prominent thing in society. In conclusion, the public's expectations for education at MTs Al-Khairiyah are very enthusiastic, there are several factors that drive the high interest of the community to entrust their children, namely the activities of the Student Da'wah Institution (LDK) and Drum Band extracurricular activities. Keywords: Community Expectations, Improvement Factors, MTs Al-Khairiyah Batu Gajah